Effect of Leadership, Competence, Education and Training Style on the Performance of Civil Servants - Nurbakti, Rezky (Universitas Negeri Makassar, 2019)
The purpose of this study: 1) To find out the influence of leadership style, competence, education and training on the performance of the Civil Servants 142 / TTG in the City of Parepare. 2) Knowing among the variables that have a dominant influence on the performance of the Civil Servants 142 / TTG in the City of Parepare. This study uses primary data and secondary data. The study population was all Civil Servants at the 142 / TTG Military Command in the City of Parepare. The sample in this study were as many as 30 permanent employees using the census method because the population was limited. Data collection is done through interviews, questionnaires, and documentation. Data analysis method uses descriptive statistical analysis, inferential analysis with regression models using SPSS Prgoram version 20. The results showed that leadership style, competence, education and training had a positive and significant effect on the performance of 142 / TTG civil servants in the city of Parepare. Of the three independent variables used, the leadership variable has a dominant influence in improving the performance of civil servants 142 / TTG in the City of Parepare.